Generasi Emas Sebagai Pilar Pembangunan: Analisis Kebijakan Perlindungan Anak Kota Malang Sebagai Perwujudan Sustainable Development Goals - Wida Aristanti; Muhammad Ikhwan (Economic Reviews Journal, 2025)
Child abuse remains a growing concern in Malang City. According to recorded data, there were 120 cases of child abuse throughout 2024, with an additional 40 cases reported by February 2025. These figures highlight the apparent failure of the contemporary local child protection system to fulfill the vision of the “Golden Generation 2045” and the 16th Sustainable Development Goal (SDG), which emphasizes peace, justice, and strong institutions. This study aims to evaluate the effectiveness of Regional Regulation (Perda) of Malang City Number 12 of 2015 concerning child protection, as one of the local legal instruments designed to prevent and address child abuse. Using a qualitative descriptive method with a discourse analysis approach, this research seeks to understand the phenomenon through the lens of policy formulation, implementation, and policy challenges. The findings reveal that the policy implementation has not had a significant impact due to weak inter-agency coordination, limited resources, and lack of policy initiation or oversight. This study recommends the importance of cross-sectoral institutional synergy, regulatory reform based on victim data, and improved capacity of policy implementers in alignment with the goals of child protection and the SDGs.